Studies in the Root System and Regeneration of Diospyros melanoxylon Roxb. - Rathore, J. S. (Indian Forester, 1971)
The present paper describes the root systems of male, female and sucker regenerated plants of Diospyros melanoxylon Roxb. Regeneration by root-suckers, in this important tree seems to be achieved by progressive growth and decay.